Toxinological, proteomic and pharmacokinetic characterization of equatorial spitting cobra (Naja Sumatrana) venom / Michelle Yap Khai Khun - Yap, Michelle Khai Khun (2013)
Naja sumatrana, the Equatorial spitting cobra, is listed as one of the medically important species in Southeast Asia and is the common spitting cobra in Peninsula Malaysia. The aims of this study are to investigate the toxinology, proteome and pharmacokinetic characteristics of N. sumatrana venom, which will contribute to management of cobra envenomation. The lethality and enzymatic activities of N. sumatrana were compared to venoms from two other regional spitting cobras: Naja sputatrix, Naja siamensis and a non-spitting cobra Naja kaouthia, which also occurs in Malaysia. Previously, the three spitting cobras were considered as belonging to one species, N. sputatrix. Results showed that the three spitting cobra venoms possess different venom composition, but all three contain basic phospholipases A2 and high content of polypeptide cardiotoxins. The proteome of N. sumatrana venom was investigated using shotgun analysis, combination of multi-dimensional chromatography and 2DE. Shotgun analysis revealed the presence of 50 individual proteins in the venom, with three finger toxins (both neurotoxins and cardiotoxins) and phospholipase A2 constituted about 38% and 36%, respectively of the types of proteins identified. The ion exchange and reverse phase HPLC revealed the presence multiple basic venom proteins including 17 identified protein toxins (8 PLA2, 4 neurotoxins and 5 cardiotoxins) whereas the Sephadex® G-50-2DE revealed the presence of another 11 high molecular weight proteins. Of the 17 protein toxins identified, only 7 exist in substantial amount, including 2 phospholipases A2, 1 short and 1 long α-neurotoxin and 3 cardiotoxins. Together these seven major venom toxins constituted 87% of total venom protein and are primarily responsible for the pathophysiological action of the venom. The pharmacokinetics of N. sumatrana and N. sputatrix venom in rabbits were also investigated. The serum toxin levels-time profile of both venoms following intravenous administration fitted a two-compartment model of pharmacokinetics with similar iv pharmacokinetic parameters. The two venoms also have comparable intramuscular bioavailability in rabbits, both approximately 40%. To further understand the pharmacokinetics of venom toxin components, the pharmacokinetics of three main N. sumatrana venom toxins (short chain α-neurotoxin, cardiotoxin and basic phospholipase A2) were also investigated. When toxins were injected intramuscularly, neurotoxin and cardiotoxin reached Cmax within 30 min, which was much faster than phospholipase A2, and the whole venom, reflecting a very rapid absorption of neurotoxin and cardiotoxin from the site of injection to systemic circulation. It was found that neurotoxin and cardiotoxin were eliminated from systemic circulation more quickly than other venom components. The neurotoxin had an intramuscular bioavailability (Fi.m. = 81.5%) much higher than phospholipase A2 (Fi.m. = 68.6%) and cardiotoxin (Fi.m. = 45.6%). The high bioavailability and short Tmax of neurotoxin when injected intramuscularly explained why neurotoxic effect is the dominant symptom in most cobra bites. In conclusion, a comprehensive understanding of the toxinology, proteome and pharmacokinetics of N. sumatrana venom and its toxins provide significant insights into the overall pathophysiological actions of the venom.